Integrating Gender in Cost-Benefit Analysis of Climate Interventions: Training Guide for the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) - Kramer, Berber; Braun, Melody; Smith Ruiz, Paulina; Taheri, Homa (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This guide provides a practical framework for conducting Cost–Benefit Analysis (CBA) of Climate Information Services (CIS) within agricultural and rural development contexts. Developed under the AICCRA–RUFORUM partnership, it equips practitioners, researchers, and students with methods to quantify the economic and social value of CIS interventions. The manual introduces key CBA principles, data requirements, valuation techniques, and participatory approaches for assessing benefits to farmers and decision-makers. Through examples, exercises, and case illustrations, the guide promotes evidence-based planning and investment in climate services, strengthening institutional capacity for integrating economic analysis into climate-smart agriculture initiatives across Africa.